An overview of implicit racial stereotype in Malaysia - Radzlan, Rohaizahtulamni; Adam Assim, Mohd Ibrani Shahrimin; Rosnon, Mohd Roslan; Baharuddin, Shamsul Amri; Gill, Sarjit S.; Zainal Badari, Shamsul Azahari (Human Resource Management Academic Research Society, 2018)
Based on the concept of social psychology, a stereotype is a scheme or general knowledge structure associated with the characteristics, attribute and behaviour of group members. Therefore, socio-cultural diversity in Malaysia has created a broad spectrum of stereotypical and prejudiced views to describe a particular ethnic group. However, discussing sensitive issues such as stereotyping and prejudice in general often give discomfort. Thus, the emergence of implicit measurements is one of the revolutions of stereotyping and attitudes to enable the assessment of attitudes towards sensitive social domains which can be evaluated through spontaneous and automatic representation that cannot be accessed by traditional questionnaires. Hence, this paper focuses on the topic briefly on the basic terminology and understanding of the measurement of implicit stereotypes adopted by the society in Malaysia.